Comparative analysis of self-reliance of athletes of different sports - A.B. Kolosov; N.Yu. Volianiuk; G.V. Lozhkin; N.A. Buniak; V.I. Osodlo (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
The purpose of the study is to identify self-reliance manifestation features among qualified athletes of different sports. Material and methods. The study participants were representatives of combat sports (boxing) n = 23, complex-coordination (gymnastics) n = 25, speed-strength (discus throw) n = 23, and also cyclic sports (swimming) n = 38. In total 109 sportsmen. The age of the respondents was from 16 to 18 years old. Comprehensive psycho-diagnostic methods diagnose self-reliance level and manifestation degree of athletes' personal qualities. Results. The results of the study confirmed our hypothesis that athletes of various sports may experience specific features of self-reliance. It has been established that self-reliance level is higher than average for representatives of combat and complex-coordinated sports. Representatives of cyclical and speed-strength sports are characterized with an average self-reliance level. Combat and complex-coordination sports are very similar according to the specifics of self-reliance expression. Self-reliance possibility data comparison among cyclical and speed-strength athletes showed their certain homogeneity. It has been revealed that only a future activities reflection is closely related to a self-reliance among boxers (Spearman rank correlation = -.478). There are two correlations in the sample of gymnastics representatives. An increase in the overall reflection index (Spearman rank correlation = -.489) and the future activities reflection index (Spearman rank correlation = -.427) leads to self-reliance decrease among gymnasts. The inhibitory effect of future activity reflection on the athletes' self-reliance level has been established empirically. We determined that self-assessment is a personal formation that actualizes self-reliance of swimmers and discus throwers. (Spearman rank correlation = .618). Conclusions. The handled comparative analysis of self-reliance of different sports athletes has verified its high informative value. Statistically significant differences recorded in the self-reliance level among of boxing, gymnastics, discus throwing and swimming athletes. The high informative value of used questionnaire allows recommending it as a screening tool during promising athletes selection.